STRATEGY FOR WINNING CANDIDATE MEMBERS OF THE PKS PARTY LEGISLATIVE IN THE 2019 ELECTIONS IN THE MALANG RAYA ELECTION AREA - Supriyanto, Didik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The presence of Prosperous Justice Party legislators quantitatively both at the central and regional levels is still considered minimal. Various attempts have been made to stipulate regulations and requirements for candidates for legislative members aimed at increasing the quantity of representation of the Prosperous Justice Party in parliament, but have not been able to realize this expectation. However, even though in terms of quantity it is still lacking, in fact there are also members of the Prosperous Justice Party legislature who at the time of their candidacy were able to prove their ability to gain sympathy from the public. By using a qualitative method, this study aims to find out what and how the winning strategy for Prosperous Justice Party Legislative Candidates in the 2019 Election in the Malang Raya constituency. The results of the study show that most of the Prosperous Justice Party Legislative Candidates in the 2019 election used several strategies, including a defensive strategy, namely a strategy carried out to maintain their voter base, there was also an offensive strategy, namely a strategy carried out to overcome threats from opponents. Apart from that, there is also an imaging strategy, namely by offering various programs that will be carried out if they are selected